Investigating Challenges of Using Ammonia as a Future Fuel for Marine Industry: A Review - Bedekar, Kishore; Oterkus, Erkan; Oterkus, Selda (Sustainable Marine Structures, 2024)
To reduce the greenhouse gases as per the forthcoming IMO rules, ammonia seems to be a suitable fuel for marine industry since it’s a hydrogen carrier and a carbon, Sulphur, and particulate matter free fuel. It has high volumetric hydrogen density, low storage pressure, and high auto ignition temperature. Ammonia can be used directly in internal combustion engines, and gas turbines.  Cracked hydrogen can be used for fuel cells. The 4th IMO Greenhouse Gas Study 2020, estimates that if no further action is taken, international shipping emissions are expected to represent 90% to 130% of 2008 emission levels by 2050. There will also be a rise in atmospheric CO2 and there is already a rise in average global sea levels from 21.9 to 23.7 between 1880 and 2010. This will affect large coastal areas of the world and island nations. The challenges for ammonia are its foul odor, corrosive nature, and being highly toxic to humans and the environment. There is also an explosion risk. Other issues are bunkering and storage on board, corrosive effect on metals, shore infrastructure, commercial and technical viability. Therefore, this study gives an overview of challenges that will be faced on board ships to use ammonia as fuel. ER